June's wild flight - Brallier, Max; Holgate, Douglas (New York : Viking, 2020)
The Midnight Blade ended with a shocking twist: a long-missing villain has returned and now has an army of the dead at his command! Jack, June, Quint, and Dirk have battled the worst kind of monsters, zombies, and cosmic servants, but an endless horde of animated skeletons is next-level. While the kids plan their next move, an unexpected threat emerges and June gets separated from her friends, dragged miles away from Wakefield to a town overgrown with monstrous vines and never-before-seen creatures. Drawing on her post-apocalyptic survival and action skills--and with the help of some odd new companions--June attempts to make her way back home. But not before she uncovers critical information about the mysterious "Tower." Information that the future of our world may hinge upon . . .
"Super rad solo episode"--Cover.
Keywords: Survival -- Juvenile fiction; Monsters -- Juvenile fiction; Humorous stories